Comparing of Three Methods of Education on Level of Knowledge towards AIDS among High School Students in Gorgan City, Northern of Iran - AA Abdollahi; E Mollaie; G Roohi (Tehran University of Medical Sciences, 2008)
Background and Aim : The Prevalence of AIDS is increasing in the World. To prevent, most scientists believe in public education. It seems that the quality of learning extensively depends on the quality of education. Since teaching method is one of the most important factors, we decided to compare the effect of three methods on the level of knowledge abut AIDS among high school students in Gorgan, northern Iran. Materials and Methods: This pre-excremental study was carried out on 88 randomly selected junior high school students in Gorgan, Iran. The subjects were asked to fill out the questionnaire before and after the two-week treatment. The data were analyzes by t-test and Tooki Test. Results: There was no significant different between control and pre and pamphlet group. While in both lecture group and combined group (lecture and pamphlet), the difference was significant .Using Tooki test, the difference between control and lecture group and between control and combined group was significant (P<0.05). Conclusions: In order to increase the student's knowledge about AIDS, According lecture method accompanying with pamphlet is one of the best procedures.